Antimicrobial Activity Test of Methanol Extract of Sygyzium cordatums Leaves on Eschericia coli and Staphylococcus aureus Using Kirby-Bauer Method - Ardhuha, Fadhlan; Harapan, Harapan (The Journal of The Indonesian Medical Students Association, 2010)
A research for determining antimicrobial activity from leaf extract of Syzygium cordatum to E. coli dan S. aureus has been conducted. This research was based on Kirby-Bauer method by using BHIB media and MHA agar. Five hundred gram of sample was dried then extracted with 1 litre methanol. The methanol extract obtained was evaporated with water bath at 50oC. Furthermore, antimicrobial activity test for E. coli and S. aureus was done in different concentration: 60%, 30%, 15%, and 7,5%. Inhibition activity of leaf extract of S. cordatum to S. aureus in 60% concentration is 16,5 mm. In concentration of 30%, 15%, and 7,5%, the inhibition activity for S. aureus were 14.5 mm, 13,5 mm, and 11 mm. Inhibition activity for positive control (Chloramphenicol) is 24,5 mm for E. coli and S. aureus. No inhibition activity was shown in negative control (methanol) for E. coli and S. aureus. There was no inhibition activity of leaf extract of S. cordatum for E. coli. In conclusion, leaf extract of S. cordatum have antimicrobial activity for S. aureus but not for E. coli. Furthermore, a research to identify this component have to be conducted.ÃÂ Key words: Antimicrobial, Sygyzium cordatum, Staphylococcus aureus, Eschericia coli, Kirby-Bauer method